2014
DOI: 10.1111/gcb.12696
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing the biodiversity impact of Neotropical oil palm development

Abstract: Oil palm agriculture is rapidly expanding in the Neotropics, at the expense of a range of natural and seminatural habitats. A key question is how this expansion should be managed to reduce negative impacts on biodiversity. Focusing on the Llanos of Colombia, a mixed grassland-forest system identified as a priority zone for future oil palm development, we survey communities of ants, dung beetles, birds and herpetofauna occurring in oil palm plantations and the other principal form of agriculture in the region--… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 59 publications
6
55
0
1
Order By: Relevance
“…The magnitude of the effects varied among continents and with land-use intensity: intensively used plantations in Asia and Africa had particularly low species richness. These results agree with previous studies that found plantations to be highly detrimental to biodiversity (Barlow et al 2007b;Brühl and Eltz 2010;Edwards et al 2010;Freudmann et al 2015;Gilroy et al 2015), especially if they are managed intensively (Faria et al 2007;Clough et al 2009;Tadesse et al 2014;Newbold et al 2015). The low biodiversity in intensive plantations is likely to reflect the lack of structural complexity and the homogeneity in the age of the stands (Fitzherbert et al 2008;Clough et al 2009;Foster et al 2011;Freudmann et al 2015).…”
Section: Discussionsupporting
confidence: 91%
“…The magnitude of the effects varied among continents and with land-use intensity: intensively used plantations in Asia and Africa had particularly low species richness. These results agree with previous studies that found plantations to be highly detrimental to biodiversity (Barlow et al 2007b;Brühl and Eltz 2010;Edwards et al 2010;Freudmann et al 2015;Gilroy et al 2015), especially if they are managed intensively (Faria et al 2007;Clough et al 2009;Tadesse et al 2014;Newbold et al 2015). The low biodiversity in intensive plantations is likely to reflect the lack of structural complexity and the homogeneity in the age of the stands (Fitzherbert et al 2008;Clough et al 2009;Foster et al 2011;Freudmann et al 2015).…”
Section: Discussionsupporting
confidence: 91%
“…; Gilroy et al . ). In Colombia, the agricultural habitat most available for conversion to oil palm is cattle pasture (Garcia‐Ulloa et al .…”
Section: Introductionmentioning
confidence: 97%
“…; Gilroy et al . ), although forest succession on these lands could be another beneficial pathway for biodiversity and carbon sequestration (Gilroy et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Seven publications were related to environmental issues such as carbon and greenhouse gases, and eight papers focused on the socioeconomic aspects and history of oil palm development in Colombia. Only three papers were related to landscape planning or land-use change [34][35][36], and, notably, just three were related to biodiversity: one included birds, dung beetles, ants and herpetofauna [37], another snakes [38], and one was related to ants [39].…”
Section: Colombian Contextmentioning
confidence: 99%
“…Gilroy et al [37] compared the diversity of ants, dung beetles, birds, and herpetofauna in oil palm plantations versus cattle pastures in the foothills of the Eastern Zone. They showed that in all four taxonomic groups, oil palm plantations have similar to or higher species richness than improved pasture.…”
Section: Biodiversitymentioning
confidence: 99%